Relación entre la cultura financiera y el nivel de endeudamiento de los emprendedores del centro comercial Sachachorro en Iquitos periodo 2024 - Varas Navas, Maria de los Angeles (2025)
This study investigates the relationship between financial culture and the level of indebtedness among entrepreneurs at the Sachachorro commercial center in Iquitos during the year 2024. Through a quantitative approach and a non experimental correlational design, data obtained from a sample of 80 entrepreneurs were analyzed. The results reveal a high positive correlation between financial culture and the level of indebtedness, with a Spearman coefficient of 0.721, although with marginal significance (p=0.051). Financial planning showed an even stronger relationship (Rho=0.7823, p=0.026), suggesting that proper planning contributes to more effective debt management. On the other hand, the relationship between budget management and indebtedness was not statistically significant (Rho=0.756, p=0.254), indicating that more efforts are needed in this area. Finally, a significant correlation was found between the capacity for indebtedness and financial culture (Rho=0.886, p=0.014), reaffirming the importance of financial education in decision-making. This study provides a foundation for future research and suggests the need to strengthen financial culture among entrepreneurs to improve their financial health and promote sustainable business development.